RF-Matrices of Arf Numerical Semigroups With Small Multiplicity - Belgin, Ö.; Gülşah, B. (Communications in Mathematics and Applications, 2023)
In this paper, multiplicity of Arf numerical semigroups and RF-matrices are given. We study Arf numerical semigroups with multiplicity of two, three, four, five and six with RF-matrices.
Keywords: ARF numerical semigroups; Frobenius number; Pseudo-Frobenius number; Multiplicity; RF-matrices